Developing Scale for Barriers to Participation in Outdoor Sports - Onur Mutlu Yaşar; Caner Özgen; Nedim Malkoç; Erdal Bal (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2020)
With the increase of leisure time, the need for people to be with nature and to do physical activity has increased. Outdoor sports activities can be defined as leisure activities which create interaction between a part of nature and the participant. Outdoor sports activities are carried out entirely following the individual's own physical, health, spiritual and social interests. Reasons for individuals to prefer outdoor sports activities and the benefits they obtained by doing outdoor sports attracted the attention of scientists. So, many kinds of research have been made on this topic. However, after observations and related literature review, it was evaluated that there are some obstacles in university students' participation in extreme sports activities. So, this study aimed to reveal a valid and reliable measurement tool for examining university students' participation barriers to outdoor sports activities. The research was designed as quantitative descriptive research. The research group of the study consisted of 342 students from Kastamonu University School of Physical Education and Sports in the 2019-2020 academic year. Exploratory and confirmatory factor analyses were made to reveal the factor structure of the scale. According to the exploratory analysis results, it was found that the scale had a structure with four factors and 12 items. The factors were named as Safety, Financial Status, Social Environment and Informing. Besides, confirmatory factor analysis results showed good fit indicates for the model (X²: 143,328, X² / df: 2,98, GFI: 94, AGFI: 90, CFI: 97, TLI: 96, IFI: 96, RMSEA: 076).